Mixing optimization of Sn-Cu-Si₃N₄ via powder metallurgy route for composite solder fabrication - Muhammad Hafiz, Zan Hazizi (Trans Tech Publications, 2014)
Link to publisher's homepage at http://www.ttp.net/